2017
DOI: 10.4049/jimmunol.1700972
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Activation by cGMP-AMP Nanoparticles Leads to Potent and Long-Acting Antiretroviral Response against HIV-1

Abstract: HIV-1 evades immune detection by the cGAS-STING cytosolic DNA sensing pathway during acute infection. STING is a critical mediator of type I interferon production, and STING agonists such as cyclic GMP-AMP (cGAMP) and other cyclic dinucleotides elicit potent immune and anti-tumor response. Here, we show that administration of cGAMP, delivered by an ultra-pH sensitive nanoparticle (PC7A), in human peripheral blood mononuclear cells (PBMCs) induces potent and long-acting antiretroviral response against several l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…Recently, it was shown that the cytosolic DNA sensor cGAS is also implicated in sensing HIV-1 infection in activated CD4 + T cells [41]. Further characterization has indicated that productive infection, particularly proviral DNA integration, is required for cGAS-dependent DNA sensing in activated CD4 + T cells [41,87]. Additionally, IFI16 has been reported to act as a specific sensor, detecting abortive HIV-1 reverse transcripts to invoke caspase-1 activation and pyroptosis in tonsillar lymphoid CD4 + T cells abortively infected with HIV, as previously described [43].…”
Section: Innate Immune Response To Hiv-1 Infection In Cd4 + T Cellsmentioning
confidence: 99%
“…Recently, it was shown that the cytosolic DNA sensor cGAS is also implicated in sensing HIV-1 infection in activated CD4 + T cells [41]. Further characterization has indicated that productive infection, particularly proviral DNA integration, is required for cGAS-dependent DNA sensing in activated CD4 + T cells [41,87]. Additionally, IFI16 has been reported to act as a specific sensor, detecting abortive HIV-1 reverse transcripts to invoke caspase-1 activation and pyroptosis in tonsillar lymphoid CD4 + T cells abortively infected with HIV, as previously described [43].…”
Section: Innate Immune Response To Hiv-1 Infection In Cd4 + T Cellsmentioning
confidence: 99%
“…Immunization in knockout mice found that the adjuvant effect of the PC7A NPs is dependent on the STING pathway, although the exact mechanism remains to be determined. Considering the effects above, the Gao group cooperated with Yan et al to load 2′,3′‐cGAMP into PC7A NPs, which were used against HIV‐1 infection . The 2′,3′‐cGAMP‐loaded PC7A NPs efficiently inhibited the replication of HIV RNA and generated a long‐lasting antiretroviral response in human peripheral blood mononuclear cells, with free cGAMP as a control.…”
Section: Sting Agonistsmentioning
confidence: 99%
“…134 Hence, delivery of exogenous type I IFN, cGAMP, or STING agonists elicited a long-lasting immune response against HIV-1, suggesting a potential new therapeutic concept. 133,135 On the other hand, Gram et al revealed that the failure of B-cells in producing type I IFN is not reversed by Epstein-Barr virus-induced STING expression in B-cells. 134 This suggests there might be one or more players in the DNA-sensing pathways that are yet to be discovered.…”
Section: A Antimicrobial Immunitymentioning
confidence: 99%